PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - rustam effendi; sahila sahila (Jurnal RATRI (Riset Akuntansi Tridinanti), 2021)
This study aims to see the Effect of Performance Financial that measured with Ratio Profitability (ROA), Leverage (DAR), and Activities (TATO) both simultaneously and partially on Profit Growth in property and real estate companies sector in 2017-2019. The sampling technique used was purposive sampling. The number of samples is 33 companies from 35 companies. This type of research is quantitative research and the type of data used is secondary data in the form of financial reports obtained through http: //www.idx.co.id. The prerequisite analysis test uses the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The data analysis technique used is multiple linear regression analysis. Based on research that has been tested using SPSS version 17.0, the results show that simultaneously ROA, DAR, and TATO have an effect on profit growth. This is evidenced by the results of the F test where from the ANOVA table that the significant value is 0.00 <0.05. Partially ROA (X1) affects profit growth,  DAR (X2) affects profit growth, and TATO (X3) has no effect on profit growth.